Knowledge, Attitudes and Practices Regarding Diabetes-Related Ocular Complications among Type 2 Diabetics in Sana’a City, Yemen - Tariek Aldoais; Abdullah Al-Mekhlafy; Lamia’a Khaled; Lamya Al-Hattami; Njood Alsharabi; Huwaida Mansoor Ahmed Al-Areqi; Bothina Alzomor (University of Science and Technology, Sana’a, Yemen, 2025)
Background: Ocular complications of diabetes mellitus (DM), including diabetic retinopathy (DR), progress silently, underscoring the need for patient awareness and screening. However, there is a lack of studies assessing diabetic patients’ knowledge, attitudes, and practices (KAPs) regarding the ocular complications of DM. Therefore, this study assessed KAPs regarding diabetes-related ocular complications among type 2 DM patients in Sana’a city to inform preventive strategies. Methods: A descriptive cross-sectional study was conducted in 2024 among 400 type 2 diabetic patients recruited via convenience sampling from public and private healthcare facilities in Sana’a city, Yemen. A pilot-tested, structured questionnaire was used to collect patients’ demographic and clinical characteristics, as well as their KAPs regarding diabetes-related ocular complications. Data were then summarized using descriptive statistics. Results: Most patients (88%) recognized the ocular effects of DM, primarily visual impairment (31%) and DR (22.4%), with fewer identifying cataracts (5.7%) or eye infections (4%). While 74.3% acknowledged the importance of regular eye exams, 39.3% were unaware of recommended frequencies, and 63% reported not undergoing regular screenings. Notably, 52.8% had never undergone dilated eye exams, 57% consulted optometrists/opticians, 37.7% never examined their eyes, and 52.8% never underwent dilated exams. Among 57 patients with DR, 98.2% received treatment recommendations, with 73.7% adhering to them and 97.6% attending follow-ups. Conclusion: In Sana’a, most type 2 diabetes patients are generally aware of diabetes’ ocular effects but lack specific knowledge of complications like DR. Many value regular eye exams, but few adhere to guidelines, rarely undergoing routine or dilated screenings. Addressing the gap between awareness and practices requires targeted education to improve preventive practices and reduce the risk of blindness.